Synergistic Reducing Effect for Synthesis of Well-Defined Au Nanooctopods With Ultra-Narrow Plasmon Band Width and High Photothermal Conversion Efficiency - Chang, Yi-Xin; Gao, Hui-Min; Zhang, Ning-Ning; Tao, Xing-Fu; Sun, Tianmeng; Zhang, Junhu; Lu, Zhong-Yuan; Liu, Kun; Yang, Bai (Frontiers in Chemistry, 2018)
Branched Au nanoparticles have attracted intense interest owing to their remarkable properties and a wide variety of potential applications in Surface-enhanced Raman spectroscopy (SERS), photothermal therapy, photoacoustic imaging, and biomedicines. The morphology and spatial arrangement of branches play the most crucial role in the determination of their properties and applications. However, it is still a synthetic challenge to control the exact arm numbers of branches with specific spatial arrangements. Here we report a facile method for the kinetically controlled growth of Au nanooctopods (NOPs) with a high yield (81%), monodispersity, and reproducibility by using the synergistic reducing effect of ascorbic acid and 1-methylpyrrolidine. The NOPs have eight arms elongated along <111> directions with uniform arm lengths. Due to their well-defined size and shape, NOPs show ultra-narrow surface plasmon band width with a full width at half maximum of only 76 nm (0.20 eV). Upon irradiation with laser, the NOPs possessed excellent photothermal conversion efficiencies up to 83.0% and photoacoustic imaging properties. This work highlights the future prospects of using NOPs with desired physicochemical properties for biomedical applications.